Uczyć się demokracji. Wykorzystane i niewykorzystane szanse udziału młodzieży w szkolnej demokracji na przykładzie wybranych szkół średnich = To learn democracy. Young people partaking in school democracy - opportunities taken and missed in selected secondary schools - Papiór, Elżbieta; Roszkowska, Martyna (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article partly presents the results of studies conducted among this Lear`s secondary school graduates from Zielona Gora. The excerpts presented in the article are a part of a wider research project entitled "School Youth towards Democracy and Future". The purpose of the inquiries is to determine whether there are differences in experiencing school democracy between the youth from "exclusive" Zielona Gora secondary schools and their peers from other schools and, if so, to what extent.
Keywords: młodzież szkolna; demokracja; badania ankietowe